2011
DOI: 10.1007/s11670-011-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib combined with cryoablation to treat unresectable hepatocellular carcinoma

Abstract: Objective: To evaluate the efficacy and tolerability of sorafenib combined with cryoablation in treating unresectable hepatocellular carcinoma (HCC).Methods: Patients with unresectable advanced HCC received cryoablation and sorafenib at a dose of 400 mg twice daily in 4-week cycles on the same day of the cryoablation. Tumor response, median overall survival and the median time to radiological progression were calculated and the toxicity was evaluated.Results: Seventy-eight patients with unresectable HCC were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The first trial of hepatocellular carcinoma (HCC) showed that median TTP in the cryoablation þ sorafenib group was longer than that in the sorafenib-only group [9.5 (8.4-13.5) months vs. 5.3 (3.8-6.9) months, p ¼ .02) .Median OS in the cryoablation þ sorafenib group was longer than that in the sorafenibonly group [12.5 (95% CI: 10.6-16.4) months vs. 8.6 (7.3-10.4) months, p ¼ .01] [29]. Another clinical trial in HCC demonstrated that cryoablation combined with sorafenib prolonged TTP and OS to 6.6 months and 12.2 months, respectively [30]. Moreover, a previous study showed that sorafenib in combination with local therapy (transarterial chemoembolization with/without cryoablation) was independently associated with longer OS and PFS in patients with advanced HCC [31].…”
Section: Discussionmentioning
confidence: 99%
“…The first trial of hepatocellular carcinoma (HCC) showed that median TTP in the cryoablation þ sorafenib group was longer than that in the sorafenib-only group [9.5 (8.4-13.5) months vs. 5.3 (3.8-6.9) months, p ¼ .02) .Median OS in the cryoablation þ sorafenib group was longer than that in the sorafenibonly group [12.5 (95% CI: 10.6-16.4) months vs. 8.6 (7.3-10.4) months, p ¼ .01] [29]. Another clinical trial in HCC demonstrated that cryoablation combined with sorafenib prolonged TTP and OS to 6.6 months and 12.2 months, respectively [30]. Moreover, a previous study showed that sorafenib in combination with local therapy (transarterial chemoembolization with/without cryoablation) was independently associated with longer OS and PFS in patients with advanced HCC [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the thematic map for the period from 2013 to 2020, the representative keywords of this research theme, in addition to “animal model,” shift to “immunotherapy” and “chemotherapy.” An increasing number of research results also show that cryoablation can have a systemic antitumor effect in synergy with immunotherapy and chemotherapy, in addition to local cytotoxic effects. [39–44] This suggests that the focus of investigators is gradually shifting toward the synergistic effects of cryoablation in combination therapy. Over time, this evolution of representative keywords is also observed in the research themes represented by prostate cancer and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cryoablation combined with sorafenib had superior clinical efficacy compared with sorafenib-only for the treatment of advanced renal cell carcinoma unsuitable for surgical treatment. Moreover, this combined therapy induced anti-tumor immunological response and significantly prolonged progression-free survival time (PFS) and overall survival (OS) without compromising patient quality of life 77 , 78 .…”
Section: Combination Cryoablation Cancer Therapiesmentioning
confidence: 99%